Antifungal and anti-inflammatory potential of eschweilenol C-rich fraction derived from Terminalia fagifolia Mart. (10th August 2019) - Rodrigues de Araújo, Alyne; Iles, Bruno; de Melo Nogueira, Kerolayne; Dias, Jhones do Nascimento; Plácido, Alexandra; Rodrigues, Artur; Albuquerque, Patrícia; Silva-Pereira, Ildinete; Socodatto, Renato; Portugal, Camila C.; Relvas, João B.; Costa Véras, Leiz Maria; et al.
Abstract: Ethnopharmacological Relevance: Folk knowledge transmitted between generations allows traditional populations to maintain the use of medicinal plants for the treatment of several diseases. In this context, the species Terminalia fagifolia Mart., native to Brazil, is used for the treatment of chronic and infectious diseases. Plants rich in secondary metabolites, such as this species and their derivatives, may represent therapeutic alternatives for the treatment of diseases that reduce the quality of life of people. Aim of the study: The aim of this study was to evaluate the antifungal and anti-inflammatory potential of aqueous fraction from ethanolic extract of T. fagifolia, with in silico study of the major compound of the fraction. Material and methods: The phytochemical study of the aqueous fraction was performed by HPLC, LC/MS and NMR. The antifungal activity was evaluated against yeasts, by determination of the minimum inhibitory concentration and minimum fungicidal concentration. The effect on Candida albicans was analyzed by AFM. The antibiofilm potential against biofilms of C. albicans was also tested. The anti-inflammatory potential of the aqueous fraction was evaluated in vivo by the carrageenan-induced paw edema and peritonitis. A microglial model of LPS-induced neuroinflammation was also studied. Further insights on the activation mechanism were studied using quantum chemistry computer simulations. Toxicity was evaluated in the Galleria mellonella and human erythrocytes models. Results: Eschweilenol C was identified as the major constituent of the aqueous fraction of the ethanolic extract of T. fagifolia . The aqueous fraction was active against all Candida strains used (sensitive and resistant to Fluconazole) with MICs ranging from 1000 to 0.4 μg/mL. By AFM it was possible to observe morphological alterations in treated Candida cells. The fraction significantly ( p < 0.05) inhibited paw edema and decreased levels of malondialdehyde induced by carrageenan. In a microglial cell model, aqueous fraction demonstrated the ability to inhibit NF-κB after induction with lipopolysaccharide. The theoretical studies showed structural similarity between eschweilenol C and indomethacin and an excellent antioxidant potential. The aqueous fraction did not present toxicity in the studied models. Conclusion: The results indicate that the aqueous fraction of T. fagifolia has potential for biomedical applications with low toxicity. This finding can be attributed to the predominance of eschweilenol C in the aqueous fraction. Graphical abstract: Image 1